2021
DOI: 10.3389/fimmu.2021.671479
|View full text |Cite
|
Sign up to set email alerts
|

Donor and Recipient Age-Mismatches: The Potential of Transferring Senescence

Abstract: In transplantation, donor and recipients frequently differ in age. Senescent cells accumulate in donor organs with aging and have the potential to promote senescence in adjacent cells when transferred into recipient animals. Characteristically, senescent cells secrete a myriad of pro-inflammatory, soluble molecules as part of their distinct secretory phenotype that have been shown to drive senescence and age-related co-morbidities. Preliminary own data show that the transplantation of old organs limits the phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 86 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Emerging research shows that lung transplant-related injury may lead to accelerated aging in the graft and that senescence can be transmitted from transplanted cells. 13,14 Finally, it is possible that some latent driver of both frailty and CLAD could explain our findings. If it turns out that 1 of the latter 2 broad potential relationships is true, it would suggest that frailty may be an early "biomarker" of CLAD risk rather than lying on the causal pathway.…”
Section: Discussionmentioning
confidence: 81%
“…Emerging research shows that lung transplant-related injury may lead to accelerated aging in the graft and that senescence can be transmitted from transplanted cells. 13,14 Finally, it is possible that some latent driver of both frailty and CLAD could explain our findings. If it turns out that 1 of the latter 2 broad potential relationships is true, it would suggest that frailty may be an early "biomarker" of CLAD risk rather than lying on the causal pathway.…”
Section: Discussionmentioning
confidence: 81%
“…After aging organ transplantation, the expression of SASP in recipients will be significantly increased to induce the aging of young cell cells, and even the aging cell population. Accumulation of mtDNA also greatly reduces the survival rate of transplanted organs ( 79 , 80 ). In the experiment of Jasper Iske et al.…”
Section: Mechanisms Of Ageingmentioning
confidence: 99%
“…This property is manifested at the organ level; for instance, in adult recipients, kidneys from young donors show an advantage in engraftment and a lower risk of rejection compared to kidneys from older donors [ 84 ]. Moreover, it has been shown that the organs of elderly donors had a negative effect on the recipients, accelerating the aging of their bodies [ 85 ].…”
Section: Cell and Genetically Modified Cell-based Therapymentioning
confidence: 99%